Endothelial NCK2 promotes atherosclerosis progression in male but not female Nck1-null atheroprone mice - Bywaters, Briana C.; Pedraza, Gladys; Trache, Andreea; Rivera, Gonzalo M. (Frontiers in Cardiovascular Medicine, 2022)
A better understanding of endothelial dysfunction holds promise for more effective interventions for atherosclerosis prevention and treatment. Endothelial signaling by the non-catalytic region of the tyrosine kinase (NCK) family of adaptors, consisting of NCK1 and NCK2, has been implicated in cardiovascular development and postnatal angiogenesis but its role in vascular disease remains incompletely understood. Here, we report stage- and sex-dependent effects of endothelial NCK2 signaling on arterial wall inflammation and atherosclerosis development. Male and female Nck1-null atheroprone mice enabling inducible, endothelial-specific Nck2 inactivation were fed a high fat diet (HFD) for 8 or 16 weeks to model atherosclerosis initiation and progression, respectively. Analysis of aorta preparations en face during disease progression, but not initiation, showed a significant reduction in plaque burden in males, but not females, lacking endothelial NCK2 relative to controls. Markers of vascular inflammation were reduced by endothelial NCK2 deficiency in both males and females during atherosclerosis progression but not initiation. At advanced stages of disease, plaque size and severity of atherosclerotic lesions were reduced by abrogation of endothelial NCK2 signaling only in males. Collectively, our results demonstrate stage- and sex-dependent modulation of atherosclerosis development by endothelial NCK2 signaling.